Arthroscopic versus Mini-Open Rotator Cuff Repair: Should We Ignore the Mini-Open Surgery - Ozcan, M. S; Varol, A; Kilinc, B. E (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2021)
PURPOSE OF THE STUDY To compare the functional and radiological results of the total arthroscopic treatment (TAT) performed due to the rotator cuff (RC) tear problem with the results of the arthroscopically assisted mini-open surgery (AAMOS). MATERIAL AND METHODS This study conducted over a two-year period included all had TAT or AAMOS. Patients were included in the study if they had undergone arthroscopic or mini-open rotator cuff repair, with a minimum of 2 years' follow-up. Patients were divided into two groups in terms of the surgical technique performed. Patients who had TAT was included into the group 1 and, AAMOS group 2. Exclusion criteria included other significant intra-articular pathology such as SLAP lesions or glenohumeral arthrosis, previous rotator cuff surgery, massive rotator cuff tears (>5 cm), and neurologic disorders such as brachial plexopathy or suprascapular neuropathy. Every patient underwent magnetic resonance imaging evaluation before surgery and at last follow-up after surgery. Acromion typed of patients were recorded. Patients were questioned for ASES and Constant score. RESULTS Fifty-eight shoulders were included in the study. Twenty-eight patients were female and 30 were male. The mean age was 55.63 ± 8.06 years. Both groups had 29 patients per each. Mean follow-up period was 26.26 ± 11.46 months. There was no statistically significant difference between the mean age and gender distribution of the groups (p > 0.05). No statistically significant difference in the follow-up period between two groups (p > 0.05). No statistically significant difference was found between the postoperative ASES measurements between the two groups (p > 0.05). There was no statistically significant difference in postoperative Constant measurements between the two groups (p > 0.05). There was no statistically significant difference between the Acromion types between the two groups (p > 0.05). No statistically significant difference was found between the both groups in terms of accompanying shoulder pathology and AC joint degeneration (p > 0.05). In the postoperative MRIs of the patients, 7 patients in the Group 2 and 6 patients in the Group 1 were found to have recurrent tears. No statistically significant difference was found (p > 0.05). DISCUSSION When compared their patients who underwent RC repair by AAMOS intervention with those treated with TAT intervention and stated that the results were satisfactory for both groups and close to each other during their 2-year follow-up regardless of the tear diameter. Rotator cuff repairing with TAT is becoming a popular method of shoulder surgery. Initial reports of outcomes with this technique have indicated similar results when compared with open techniques, with less perioperative morbidity. Patients with RC tears treated by TAR, the shoulder range of motion was achieved in a shorter time and the rate of development of fibrous ankylosis was found to be lower. We performed the same configuration for the repair technique that may avoid to differ the results. Additionlay, all patients in study had the same rehabilitation protocol not to differ the results. Our study demonstrated similar results, with no differences noted in clinical outcomes between the TAT and the AAMOS for all scoring scales evaluated. Our experience with TAT notes a steep learning curve for proper technique. Certainly, surgeons may attempt a TAT, knowing that the patient's long-term outcome will not differ if the AAMOS is needed. CONCLUSIONS It must be kept in mind that both surgical methods may provide satisfactory results; the decision regarding which method should be used must be based on the skills, experience and technical oppurtunities of the orthopedic surgeon. However, any of the surgical technique is chosen, smilar excellent clinical results can be achieved. Key words: rotator cuff, mini-open surgery, total arthroscopic repair, cuff tear, Constant score, ASES score.
Keywords: výsledek terapie; Male; Shoulder Joint; rozsah kloubních pohybů; rotátorová manžeta; Range of Motion, Articular; poranění rotátorové manžety; akromion; mužské pohlaví; artroskopie; Arthroscopy; Treatment Outcome; lidé; ženské pohlaví; Rotator Cuff; ramenní kloub; Humans; Acromion; Female; lidé středního věku; Middle Aged; Rotator Cuff Injuries